Firstly, let's take first factor:
(y^3)^2 = y^(3*2) = y^6
and then:
y^6 * y^7 = y^(6 + 7) = y^13
Answer:
The answer is 6.3
Step-by-step explanation:
Answer:
-2
Step-by-step explanation:
First, solve so that y is alone on its side of the equation by dividing both sides of the equation by 12.
12y=(-24)x
y=(-2)x
Therefore, the slope must be -2.
9514 1404 393
Answer:
x^2 -4x +2 = 0
Step-by-step explanation:
The other root is the conjugate of the given one, so is 2-√2. The quadratic equation in factored form is then ...
(x -2-√2)(x -2+√2) = 0
Expanding this, we get ...
(x -2)^2 -(√2)^2 = 0
x^2 -4x +4 -2 = 0
x^2 -4x +2 = 0 . . . . the equation you're looking for